(untitled) (Research, Society and Development, 2021)
• Oral Epidermoid Carcinoma (OEC) is the sixth most common type of cancer worldwide, affecting mainly male patients over 45, smokers and chronic drinkers. Its prevalence among younger individuals and in women, however, has gradually increased over the past few years. This neoplasm presents an aggressive biological behavior, with high recurrence rates and metastatic potential, especially when diagnosed late. The therapeutic scheme is chosen based on the clinical stage of each case. This paper aims to report an OEC case diagnosed by the Oral Health Team of a Family Health Unit (FHU) in a young patient unexposed to the risk factors most strongly associated with the disease.